Extreme eutrophication and salinisation in the Coorong estuarine-lagoon ecosystem of Australia's largest river basin (Murray-Darling) - L.M. Mosley; S. Priestley; J. Brookes; S. Dittmann; J. Farkaš; M. Farrell; A.J. Ferguson; M. Gibbs; M. Hipsey; J. Huang; O. Lam-Gordillo; S.L. Simpson; et al. (Marine Pollution Bulletin, 2023)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Estimating Mangrove Tree Biomass and Carbon Content: A Comparison of Forest Inventory Techniques and Drone Imagery - Alice R. Jones; Ramesh Raja Segaran; Kenneth D. Clarke; Michelle Waycott; William S. H. Goh; Bronwyn M. Gillanders (Frontiers in Marine Science, 2020)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Characterisation of polymorphic microsatellite markers in the widespread Australian seagrass, Posidonia australis Hook. f. (Posidoniaceae), with cross-amplification in the sympatric P. sinuosa - E. A. Sinclair; J. Anthony; G. T. Coupland; M. Waycott; M. D. Barrett; R. L. Barrett; M. L. Cambridge; M. J. Wallace; K. W. Dixon; S. L. Krauss; G. A. Kendrick (Conservation Genetics Resources, 2009)

Relative information content of polymorphic microsatellites and mitochondrial DNA for inferring dispersal and population genetic structure in the olive sea snake, Aipysurus laevis - V. LUKOSCHEK; M. WAYCOTT; J. S. KEOGH (Molecular Ecology, 2008)
Polymorphic microsatellites are widely considered more powerful for resolving population structure than mitochondrial DNA (mtDNA) markers, particularly for recently diverged lineages or geographically proximate populations. Weaker population subdivision for biparentally inherited nuclear markers than maternally inherited mtDNA may signal male‐biased dispersal but can also be attributed to marker‐specific evolutionary characteristics and sampling properties. We discriminated between these competing explanations with a population genetic study on olive sea snakes, Aipysurus laevis . A previous mtDNA study revealed strong regional population structure for A. laevis around northern Australia, where Pleistocene sea‐level fluctuations have influenced the genetic signatures of shallow‐water marine species. Divergences among phylogroups dated to the Late Pleistocene, suggesting recent range expansions by previously isolated matrilines. Fine‐scale population structure within regions was, however, poorly resolved for mtDNA. In order to improve estimates of fine‐scale genetic divergence and to compare population structure between nuclear and mtDNA, 354 olive sea snakes (previously sequenced for mtDNA) were genotyped for five microsatellite loci. F statistics and Bayesian multilocus genotype clustering analyses found similar regional population structure as mtDNA and, after standardizing microsatellite F statistics for high heterozygosities, regional divergence estimates were quantitatively congruent between marker classes. Over small spatial scales, however, microsatellites recovered almost no genetic structure and standardized F statistics were orders of magnitude smaller than for mtDNA. Three tests for male‐biased dispersal were not significant, suggesting that recent demographic expansions to the typically large population sizes of A. laevis have prevented microsatellites from reaching mutation‐drift equilibrium and local populations may still be diverging.

Phylogeography of the olive sea snake, Aipysurus laevis (Hydrophiinae) indicates Pleistocene range expansion around northern Australia but low contemporary gene flow - V. LUKOSCHEK; M. WAYCOTT; H. MARSH (Molecular Ecology, 2007)
Pleistocene sea‐level fluctuations profoundly changed landmass configurations around northern Australia. The cyclic emergence of the Torres Strait land bridge and concomitant shifts in the distribution of shallow‐water marine habitats repeatedly sundered east and west coast populations. These biogeographical perturbations invoke three possible scenarios regarding the directions of interglacial range expansion: west to east, east to west, or bidirectional. We evaluated these scenarios for the olive sea snake, Aipysurus laevis, by exploring its genetic structure around northern Australia based on 354 individuals from 14 locations in three regions (Western Australia, WA; Gulf of Carpentaria, GoC; Great Barrier Reef, GBR). A 726‐bp fragment of the mitochondrial DNA ND4 region revealed 41 variable sites and 38 haplotypes, with no shared haplotypes among the three regions. Population genetic structure was strong overall, φ ST = 0.78, P

Molecular Discrimination of Perna (Mollusca: Bivalvia) Species Using the Polymerase Chain Reaction and Species-Specific Mitochondrial Primers - D. Blair; M. Waycott; L. Byrne; G. Dunshea; C. Smith-Keune; K. M. Neil (Marine Biotechnology, 2006)

AFLP diversity within and between populations of the Caribbean seagrass Thalassia testudinum (Hydrocharitaceae) - Waycott M.; Barnes P. (Marine Biology, 2001)